Baseline anticholinergic burden from medications predicts poorer baseline and long‐term health‐related quality of life in 16 675 men and women of EPIC‐Norfolk prospective population‐based cohort study. Issue 2 (5th August 2020) - Yrjana, Kaisa R.; Neal, Samuel R.; Soiza, Roy L.; Keevil, Victoria; Luben, Robert N.; Wareham, Nicholas J.; Khaw, Kay‐Tee; Myint, Phyo Kyaw
Abstract: Purpose: Previous studies investigating the association between anticholinergic burden (ACB) and health‐related quality of life (HRQoL) showed conflicting results and focused on older adults or specific patient groups only. Methods: Participants from the European Prospective Investigation of Cancer‐Norfolk study were divided into three groups according to their ACB from medications at baseline, representing ACB scores of 0, 1 and ≥2. Outcomes of interest were the physical and mental component summary scores (PCS and MCS) of the Short Form‐36, collected at 18 months from the baseline and again after a mean 13 years of follow‐up. Linear regression and logistic regression for cross‐sectional and longitudinal associations between ACB and HRQoL were constructed adjusting for potential confounders. Results: A total of 16 675 participants, mean age 58.9 ± 9.1 years (55.6% female) and 7133 participants, mean age at follow‐up 69.1 ± 8.7 years (56.8% female), were included in the cross‐sectional and longitudinal analyses, respectively. In cross‐sectional analysis, higher anticholinergic burden was associated with higher odds of being in the lowest quartile of PCS (ACB = 1; OR, 1.85[1.64, 2.09] and ACB ≥ 2:2.19[1.85, 2.58] and MCS (ACB = 1:1.47[1.30, 1.66] and ACB ≥ 2:1.68[1.42, 1.98]). In longitudinal analysis, higher anticholinergic burden was similarly associated with higher odds of being in the lowest quartile of PCS (ACB = 1:1.56[1.24, 1.95] and ACB ≥ 2:1.48[1.07, 2.03]) compared with ACB 0 group. The association with MCS scores did not reach statistical significance. Conclusion: The use of anticholinergic medications is associated with both short and long‐term poorer physical functions but association with mental functioning appears more short‐term.